Bioremediation of Nickel and Iron from Solutions by Non-pathogenic Microorganisms - Elizabeth, K.M.; Prem Sajani, P. (Asian Journal of Chemistry, 2010)
Bioremediation of nickel and iron from artificially introduced solutions by various nonpathogenic microorganisms was tested. The concentration of metal used was 100 mg/L. Viable Pseudomonas species and Bacillus species could remove 56.24 and 56.8% of nickel, respectively. There was 11.1-96.86% removal of iron by viable microorganisms, Aspergillus species with highest and Saccharomyces species with lowest percentage removal. The biosorption technique showed a range of 54.32-87.2% removal of nickel, with highest removal by Bacillus species. The biosorption of iron ranged from 60-100% with highest percentage removal by Aspergillus species. The percentage removal of nickel ranged from 54.8-92.4 and iron removal ranged from 73-95.68% by immobilization technique. The results of the present study indicate that these microorganisms are potential to remove nickel and iron from polluted waters, soils, industrial effluents, agricultural and municipal wastes.